One Anastomosis Gastric Bypass Surgery: Consequences Over Ascorbic Acid, Cobalamin, Calciferol, and Calcium (Bangladesh Journal of Medical Science, 2023)
Background: Nutrient deficiency after malabsorptive bariatric procedure is a common phenomenon. The study aims to determine the prevalence of nutritional insufficiencies (specific with Ascorbic acid, Cobalamin, calciferol and calcium) in obese population opting for One Ananstomosis Gastric Bypass surgery (OAGB), and also to understand the association of these nutrients with change in Body Mass Index (BMI) after the surgery.Methods: One hundred fifty subjects comprising males and females aged 20-60 years were randomly selected at a bariatric center in India. Subjects belonged to both grade III and grade II obesity. Plasma aa, serum vitB12, serum VitD3 and serum calcium concentrations were prospectively assessed at 0m, 3m, and 6m of surgery through high-performance liquid chromatography.Result: The values of nutrients beyond the standard levels are considered as deficiency. Both follow up values showed a significant increase in cobalamin, Calciferol, and ascorbic acid levels compared to baseline data.Conclusion: Nutrition depletion and deficiency are often seen in post bariatric cases. The contributing factors included high BMI, food intolerance, and non-adherence to supplements and correct dietary regimens. With the correction of weight and comorbidities, the levels also showed a stable and positive level.Bangladesh Journal of Medical Science Vol. 22 No. 03 July’23 Page : 695-708